Bryophyte propagule bank in the Yukidori Valley, Langhovde, Antarctica - Eri Ayukawa; Satoshi Imura; Hiroshi Kanda (National Institute of Polar Research, 2002)
Distribution, species composition and possibilities of germination of the propagule bank of moss in Antarctic soils were investigated by cultural experiments. Soil samples were collected in the Yukidori Valley, Antarctica, and were incubated under laboratory conditions. After several weeks, fungi, algae and mosses were observed in the samples. The dominant species within the germinated moss shoots was Bryum pseudotriquetrum s. lat.; in fact, this species was the only moss species at the study site. Shoots of Ceratodon purpureus and Pottia heimii appeared rarely in the general area, but were not observed at all at the study site. Vegetative propagules such as fragments of shoots were frequently found in the soils, most of the germinated shoots sprouted from such propagules. These propagules were thought to be important for colonization at the site. A relatively large number of shoots of B. pseudotriquetrum appeared from the samples collected from the ground near the vegetation. Most of the propagules of B. pseudotriquetrum in the soils were thought to be dispersed from nearly communities, whereas some propagules such as C. purpureus and P. heimii were thought to be dispersed from more distant moss communities.